Factors associated with HIV seroconversion in gay men in England at the start of the 21st century. Issue 1 (14th November 2007) - Macdonald, N; Elam, G; Hickson, F; Imrie, J; McGarrigle, C A; Fenton, K A; Baster, K; Ward, H; Gilbart, V L; Power, R M; Evans, B G
Abstract : Objectives: To detect and quantify current risk factors for HIV seroconversion among gay men seeking repeat tests at sexual health clinics. Design: Unmatched case control study conducted in London, Brighton and Manchester, UK. Methods: 75 cases (recent HIV positive test following a negative test within the past 2 years) and 157 controls (recent HIV negative test following a previous negative test within the past 2 years) completed a computer-assisted self interview focused on sexual behaviour and lifestyle between HIV tests. Results: Cases and controls were similar in socio-demographics, years since commencing sex with men, lifetime number of HIV tests, reasons for seeking their previous HIV tests and the interval between last HIV tests (mean = 10.5 months). Risk factors between tests included unprotected receptive anal intercourse (URAI) with partners not believed to be HIV negative (adjusted odds ratio (AOR) and 95% confidence interval 4.1, 1.8 to 9.3), where increased risk was associated with concomitant use of nitrite inhalants, receiving ejaculate and increasing numbers of partners. Independent risk was also detected for unprotected insertive anal intercourse (UIAI) with more than one man (AOR 2.7, 1.3 to 5.5) and use of nitrite inhalants (AOR 2.4, 1.1 to 5.2). Conclusions: HIV serodiscordant unprotected anal intercourse remains the primary context for HIV transmission among gay men, with increased risk associated with being the receptive partner, receiving ejaculate and use of nitrite inhalants. Although the HIV transmission risk of URAI is widely acknowledged, this study highlights the risk of UIAI and that nitrite inhalants may be an important facilitator of transmission when HIV exposure occurs.